1988
DOI: 10.1159/000116585
|View full text |Cite
|
Sign up to set email alerts
|

Functional-Anatomical Studies of Neural Control of Heart Rate in Goldfish

Abstract: Neural control of heart rate (HR) was investigated in goldfish, Carassius auratus, using electrical stimulation of the brain. Three types of HR response were evoked by stimulation: HR decreases during stimulation (type I); HR increases during stimulation (type II), and HR decreases during stimulation, followed by increased rates at the offset (type III). Type I bradycardias were evoked by stimulation of the preoptic area and diencephalon, specifically in the ventral thalamus-dorsal hypothalamus transitional ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This would be a similar situation to that in certain mammals where CA-containing neurons in the caudal ventrolateral medulla are known to project to the (visceral afferent) nucleus tractus solitarius [Blessing et a!., 1981]. A role in control of autonomic function by catecholaminergic neurons in the medullary tegmentum of teleosts is indicated by studies where electrical stimulation of this region evokes profound changes in heart rate [Hornby and Demski, 1988]. This is interesting be cause of the role of the ventrolateral medulla, includ ing the A1 area, in control of cardiovascular function in mammals [Blessing and Reis, 1982].…”
Section: Th-and Dbh-ir Cell Bodiesmentioning
confidence: 72%
“…This would be a similar situation to that in certain mammals where CA-containing neurons in the caudal ventrolateral medulla are known to project to the (visceral afferent) nucleus tractus solitarius [Blessing et a!., 1981]. A role in control of autonomic function by catecholaminergic neurons in the medullary tegmentum of teleosts is indicated by studies where electrical stimulation of this region evokes profound changes in heart rate [Hornby and Demski, 1988]. This is interesting be cause of the role of the ventrolateral medulla, includ ing the A1 area, in control of cardiovascular function in mammals [Blessing and Reis, 1982].…”
Section: Th-and Dbh-ir Cell Bodiesmentioning
confidence: 72%
“…This aspect of the experimental design was motivated by previous literature [31], [32], which suggests that the direction (increase versus decrease) of HR responses (see below) to fear conditioning can depend on whether the animal perceives that it has some control on the outcome of CS+ during training. Any vocalizations emitted by the animal, which crossed a set threshold, were acquired by a high frequency microphone (model 9569, ACO Pacific Inc. USA) and filtered between 1 and 100 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Exogenous GRP within the third ventricle may stimulate GRP neurons or other neurons that project their axons to the cardioventilatory centers within the brainstem (Le Mével et al, 2012). In the goldfish, functional-anatomical studies have demonstrated the existence of a neural pathway from the preoptic area to the dorsal motor nucleus of the vagus controlling concomitantly ventilation and ƒH (Hornby and Demski, 1988). The neurochemicals involved in this pathway were not determined.…”
Section: Discussionmentioning
confidence: 99%